E2511, a novel small compound TrkA allosteric modulator, induces a specific trophic signaling via direct binding to TrkA, and can reverse the loss of choline acetyltransferase (ChAT) positive neurons in transgenic models of AD. (31st December 2021) - Tomioka, Takeyasu; Moriyama, Yoshiyuki; Hiramatsu, Naoki; Kosasa, Takashi; Kondo, Keita; Wakita, Hisashi
Abstract: Background: Loss of cholinergic neurons in Alzheimer's disease (AD) is an early pathogenic event correlated with cognitive impairment. Nerve growth factor (NGF) plays a major role in the maintenance and function of cholinergic neurons. Decrease in NGF‐Tropomyosin receptor kinase A (TrkA) induced trophic signaling contributes to cholinergic neurodegeneration and cognitive decline during the course of AD. The activation of the trophic signaling could be a promising therapy for AD, reinnervating basal forebrain cholinergic neurons. We provide evidence that our novel small compound E2511 is TrkA allosteric modulator showing an increase in specific trophic signaling via direct binding to TrkA. Method: E2511 was characterized in several in vitro assays such as NMR assay for detecting binding to TrkA and biochemical studies for evaluating the phosphorylation level of TrkA in each site using rat primary septal neurons. The in vivo effects of the compound on TrkA signaling were investigated in human Tau P301S transgenic mice (Tau tg mice) by biochemical studies such as western blot analysis, while assessing whether the compound induces hyperalgesia in behaviour studies and pain‐related signaling in normal and pain model rats. Moreover, the trophic effect of the compound on cholinergic neurons was investigated in Tau tg mice. Result: E2511 enhanced phosphorylation level of TrkA in the presence of NGF via direct binding to TrkA in rat primary neurons, and phosphorylation level of each site of TrkA induced by the compound was different from that of NGF. In vivo experiments demonstrated that oral administration of E2511 elevated trophic signaling in the septum, while induction of hyperalgesia was not detected. Furthermore, chronic administration of E2511 reversed the loss of ChAT‐positive cells in Tau tg mice by therapeutic treatment. Conclusion: E2511 enhances specific trophic signaling by altering TrkA signaling as specific allosteric modulator via direct binding to TrkA, and E2511 shows the reinnervative effect on cholinergic neurons through activation of TrkA signaling without induction of NGF‐like adverse effect.